Energy Intensity Analysis of Coal and Electricity in The Manufacturing Industry Sector in Indonesia 2007–2015 - Olive Alexander Ambardhy (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2022)
This study has two objectives, first to decompose and compare the energy intensity of coal and electricity in the manufacturing sector in Indonesia. The second is to analyze what factors influence the energy intensity of the manufacturing industry sectors. The methods used in achieving these objectives are decomposition analysis and panel data regression analysis. The results of the decomposition analysis show that the efficiency effect dominates changes in energy intensity than the activity effect. Furthermore, the results of panel data analysis show that the variables of energy prices, intensity of machine maintenance and repair, intensity of raw materials, and intensity of machines have a significant effect on changes in energy intensity in the manufacturing sector in Indonesia in the time span from 2007 to 2015.